2017
DOI: 10.1016/j.drugalcdep.2017.05.045
|View full text |Cite
|
Sign up to set email alerts
|

Regular cannabis and alcohol use is associated with resting-state time course power spectra in incarcerated adolescents

Abstract: Cannabis and alcohol are believed to have widespread effects on the brain. Although adolescents are at increased risk for substance use, the adolescent brain may also be particularly vulnerable to the effects of drug exposure due to its rapid maturation. Here, we examined the association between cannabis and alcohol use duration and resting-state functional connectivity in a large sample of male juvenile delinquents. The present sample was drawn from the Southwest Advanced Neuroimaging Cohort, Youth sample, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 82 publications
(103 reference statements)
0
18
0
Order By: Relevance
“…Task-based fMRI meta-analysis has reported PCC areas in the DMN to be affected in substance seekers (Blest-Hopley, Giampietro, & Bhattacharyya, 2018;Yanes et al, 2018). The rs-fMRI analysis revealed that longer use of cannabis is associated with decreased low frequency power of the DMN (Thijssen et al, 2017). The PCC, a key region in the DMN is responsible for self-consciousness and self-referential mental thoughts (Andrews-Hanna, Reidler, Sepulcre, Poulin, & Buckner, 2010;Andrews-Hanna, Smallwood, & Spreng, 2014;Buckner & Carroll, 2007;Cavanna & Trimble, 2006;Fransson & Marrelec, 2008;Leech & Sharp, 2013;Raichle et al, 2001;Spreng, Mar, & Kim, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Task-based fMRI meta-analysis has reported PCC areas in the DMN to be affected in substance seekers (Blest-Hopley, Giampietro, & Bhattacharyya, 2018;Yanes et al, 2018). The rs-fMRI analysis revealed that longer use of cannabis is associated with decreased low frequency power of the DMN (Thijssen et al, 2017). The PCC, a key region in the DMN is responsible for self-consciousness and self-referential mental thoughts (Andrews-Hanna, Reidler, Sepulcre, Poulin, & Buckner, 2010;Andrews-Hanna, Smallwood, & Spreng, 2014;Buckner & Carroll, 2007;Cavanna & Trimble, 2006;Fransson & Marrelec, 2008;Leech & Sharp, 2013;Raichle et al, 2001;Spreng, Mar, & Kim, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Nicotine (a key ingredient of tobacco) was also associated with decreased activity in the regions of DMN (Tanabe et al, 2011) and low overall functional connectivity (Cheng et al, 2019). From the vast pool of scientific studies, it can be inferred that tobacco and drugs intake, along with marijuana and alcohol use are associated with differences in rs time courses (Cheng et al, 2014), and are possibly making adolescents more vulnerable to psychiatric and other disorders (Thijssen et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Task-based fMRI meta-analysis has reported PCC areas in the DMN to be affected in substance seekers (Blest-Hopley, Giampietro, & Bhattacharyya, 2018;Yanes et al, 2018). The rs-fMRI analysis revealed that longer use of cannabis is associated with decreased low frequency power of the DMN (Thijssen et al, 2017). The posterior cingulate cortex (PCC), a key region in the DMN is responsible for self-consciousness and self-referential mental thoughts (Andrews-Hanna, Reidler, Sepulcre, Poulin, & Buckner, 2010;Andrews-Hanna, Smallwood, & Spreng, 2014;Buckner & Carroll, 2007;Cavanna & Trimble, 2006;Fransson & Marrelec, 2008;Leech & Sharp, 2013;Raichle et al, 2001;Spreng, Mar, & Kim, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Nicotine (a key ingredient of tobacco) was also associated with decreased activity in the regions of DMN (Tanabe et al, 2011) and low overall functional connectivity (Cheng et al, 2019). From the vast pool of scientific studies, it can be inferred that tobacco and drugs intake, along with marijuana and alcohol use are associated with differences in resting state time courses (Cheng et al, 2014), and are possibly making adolescents more vulnerable to psychiatric and other disorders (Thijssen et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…A longitudinal study of resting state functional connectivity comparing adolescence cannabis users and non-users found decreased connectivity between the ACC and the dorsolateral and orbital frontal cortices in adolescent cannabis users across 18 months of cannabis use, while connectivity between the ACC and the superior frontal gyrus increased over time in healthy controls (97). Examination of resting state connectivity between the central executive network, default mode network and sensory networks in a cohort of adolescents found decreased connectivity in all networks as a function of longer duration of cannabis use (98). Similar alterations were seen in connectivity between the striatum and frontal-limbic circuit during a comparison of adolescent cannabis users with non-users, in addition to attenuation of the negatively correlated functional connectivity between the striatum and the fusiform gyrus, a region that serves a critical role in the recognition of significant visual features; it is important to note that some of these observations appeared to normalize after abstinence (95).…”
Section: Studies Investigating Brain Functional Alterations Associatementioning
confidence: 94%